Outside the Economy: Women's Work and Feminist Economics in the Construction and Critique of National Income Accounting. Issue 3 (4th May 2018) - Messac, Luke
ABSTRACT: Concerns about women's work were present at the advent of the modern method of national income accounting, and they have featured prominently in the most radical critiques of this method. During and after the Second World War, Phyllis Deane, a young researcher working under the supervision of Richard Stone, Austin Robinson and Arthur Lewis, grappled with the conceptual difficulties involved in measuring the 'national' incomes of mostly rural subsistence colonies in British central Africa. In constructing her estimates, Deane relied heavily on a multidisciplinary survey of nutrition conducted in interwar Nyasaland. Deane's work was essentially an exercise in reductionism and bounding; she sought to extract from these data a single monetary estimate of production. Yet Deane also proved unwilling to exclude too much. She broke with her advisors' favoured convention that activities not involved in market exchange should be excluded from the national income. Successive national income accountants around the world would reach disparate conclusions on method, particularly on the question of the 'production boundary'—that is, the dividing line between those productive activities that would be included in the national income and those that would not. This issue became most contentious in the sphere of 'non-monetary' or 'subsistence' production performed mostly by female producers. While some statisticians included firewood collection, beer brewing and cooking, many others thought such activities beyond the bounds of 'the economy'. Early decisions about the status of non-monetary production influenced the international standards enshrined in the United Nations System of National Accounts, first published in 1953. Beginning in the 1970s, second-wave feminists criticised the invisibility of women's work in national income estimates. These critiques helped spur the inclusion of non-monetary activities in the accounts of many nations. Yet by the 1990s, many feminist critics—most notably New Zealand-born political economist Marilyn Waring—sought to move beyond GDP as a measure of welfare. These feminists called instead for greater reliance on measures such as the Human Development Index and time-use surveys. These measures may have appeared new, but they required the same multidisciplinary and intensive methods as Nyasaland's interwar nutrition survey, which had served as the substrate for the earliest calculation of a 'colonial national' income. Drawing upon archives in the United Kingdom, Malawi and the United States, this paper argues that feminist economists and women's work were central to both the post-war construction and the late-twentieth century critique of national income.